How Should the Paradigm of Islamic Economic Research Be Understood? - Sjafruddin, Sjafruddin; Zainuri, Hamzah (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2025)
Islamic economics is still a relatively new field within academic discourse, especially when compared to other more established branches of Islamic sciences. The practice of Islamic economics in the market has spurred further investigation and research to address the emerging challenges and issues. A key problem that arises is the dominance of quantitative-positivistic approaches, which have come to be regarded as "mainstream," while alternative approaches are often considered "non-mainstream." The positivist paradigm, with its emphasis on value-neutrality, tends to distance research from the human values that define economic actors as spiritual beings. In response, the integration-interconnection paradigm seeks to position Islamic economics within a framework that incorporates the objectification of religious ethics, thus aligning economic practice with spiritual and ethical considerations.